Role of Micro- and Mesosystems in Shaping an Adolescent - Chandra Sekaran, Varalakshmi; Kamath, Veena G; Ashok, Lena; Kamath, Asha; Hegde, Asha P; Devaramane, Virupaksha (Journal of Nepal Paediatric Society, 2018)
Adolescence is a vulnerable period in an individual’s life during which several physiological and psychological changes occur. Increasingly, across the globe, there is increasing incidence of mental health and behavioural problems documented, especially among the youth. The WHO states that mental health conditions and delinquent behaviours contribute significantly to the global disease burden. The transition from adolescence to adulthood is also marked by increasing manifestation of emotional and behavioural disorders with first episodes making their appearance in early adolescence. This review attempts to delve into the influence of microsystem and mesosystems as described by Bronfenbrenner on adolescent behaviours.